HALAL FOOD INDUSTRY INNOVATION IN INDONESIA - Ach Faqih Supandi; Istiadah Alhumairoh; Fais Faizul Hannan; Sigit Kusbiantoro (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2022)
Indonesia is a country that has great potential for the development of the halal industry. This is certainly one of the biggest opportunities in increasing the halal food industry with the influence of Indonesia's large Muslim population. Indonesia accounts for 12.7% of the world's Muslim population.This research is a descriptive study with qualitative and phenomenological methods. While the data used is library data which is supported by several articles relating to this research. Then analyze the data obtained by providing a descriptive explanation of the form of text, images, and symbols that are connected. The purpose of this study.To increase awareness about halal products in Indonesia, it will be more optimal if there is a government role in handling the development of these products directly and sustainably. One of the methods in developing halal food in Indonesia is to socialize the advantages of halal products that are conceptualized and comply with the criteria of Islamic sharia. This can also be done by researchers, participants, media (mass and print) and educational institutions that are still in the realm of Islam